Simulasi Perambatan Gelombang Georadar (GPR) pada Suatu Media Berlapis - Suprianto, Agus (Jurnal Fisika FLUX, 2009)
The simulation of the wave propagation of the radar in the sub-surface was very important to be understood before being carried out of field acquisition,to maximize the design of the acquisition and to optimized radar gram dataâs.One of the approaches in the simulation of the data was to use propagationmodeling of the electromagnetic wave by using the Finite Difference TimeDomain solution (FDTD). Modeling of electromagnetic wave propagation in theGPR requires a solution of Maxwellâs equations or present a finite-differencetime-domain (FDTD) solution of Maxwellâs that permit accurate computation ofthe radiated field from a transmitting antenna. Propagating through the air-earthinterface, scattering by subsurface targets and reception of the scattered fieldsby receiving antenna. This technique is second-order accurate in time andfourth-order accurate in space. In this paper, I demonstrate the synthetic radargram by applying this technique to two-dimensional examples from a subsurfaceof stratified media.